Social Partners in the Green Transition of the EU - Anke Hassel; Kilian Weil (Vierteljahrshefte zur Wirtschaftsforschung, 2023)
The paper explores the role of social partnership for facilitating processes to reduce greenhouse gas emissions in Europe. Social partnership can help to facilitate the transition to lower emissions by negotiating the costs and benefits of climate reducing policies with the workers affected. At the same time, social partnership is stronger in sectors, which have high emissions and might be tempted to reduce the speed of phasing out high emission production processes. The paper uses data from the Structure of Earnings Survey to examine the relationship between bargaining coverage, unionization, wages and industry emissions in EU member states. It analyses these relationships in the context of different growth trajectories towards the knowledge economy. It finds that high-emitting industries tend to have higher profits, wages and lower wage inequality than others. Brown jobs, however, are not better jobs, but benefit from collective bargaining. At the same time, there are significant differences between the member states of the European Union. The paper concludes by discussing how social partnership deals with the dilemma of being rooted in fossil fuel industries while negotiating change. – – Der Beitrag untersucht die Rolle der Sozialpartnerschaft zur Reduzierung von Treibhausgasemissionen in Mitgliedsstaaten der Europäischen Union. Einerseits können die Sozialpartner dazu beitragen den Übergang zu niedrigeren Emissionen zu erleichtern, indem sie mit den betroffenen Arbeitnehmern über die Kosten und den Nutzen von Maßnahmen zur Verringerung des Klimawandels verhandeln. Andererseits ist die Sozialpartnerschaft in Sektoren mit hohen Emissionen stärker ausgeprägt. Das könnte dazu führen, dass Sozialpartner versuchen, die Geschwindigkeit zur Reduzierung emissionsintensiver Produktionsprozesse zu verringern. Wir verwenden Daten aus der europäischen Verdienststrukturerhebung, Structure of Earnings Survey, um die Beziehung zwischen Tarifbindung, gewerkschaftlicher Organisation, Löhnen und Industrieemissionen in den EU-Mitgliedstaaten zu untersuchen. Wir finden, dass Sektoren mit hohen Emissionen höhere Gewinne, Löhne und geringere Lohnungleichheit aufweisen. Berufe mit hohen Emissionen sind hingegen nicht besser bezahlt. Gleichzeitig gibt es deutliche Unterschiede zwischen den Mitgliedsstaaten der Europäischen Union. Abschließend erörtern wir, wie die Sozialpartnerschaft mit dem Dilemma umgeht, in den stark fossilen Industrien verwurzelt zu sein und gleichzeitig den Wandel zu verhandeln.
Keywords: J21; J31; J52; 330; Green transition; collective bargaining; social partnership